The Dynamics of Corruption with the Ratchet Effect - Jay Pil Choi; Marcel Thum (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper provides a simple model of corruption dynamics with the ratchet effect. As in Shleifer and Vishny [1993], we consider the sale of government property (entry permit) by government officials as the prototype of corruption activities. In a dynamic version of the Shleifer-Vishny model, corrupt officials have ex post the incentive to price discriminate entrepreneurs based on the entry decisions made in an earlier period. We show that the inability of government officials to commit to future money demands induces the ratchet effect in that entrepreneurs have incentives to delay entry in order to receive a discount in the permit price later. The ex post opportunism erodes the official's extortion power and reduces his revenues from selling permits. Even though the dynamic setting leaves the corrupt official with less extortion power, we cannot rule out the possibility that the official's ability to apply dynamic discrimination decreases the intertemporal aggregate social welfare. We also explore the effect of the official's tenure stability on the extent of corruption. This allows us to identify circumstances under which the often observed practice of job rotation can help mitigate corruption.
Keywords: 330; Corruption dynamics; ratchet effect; ex post opportunism; dynamic consistency